Peningkatan Kemampuan Critical Thinking Siswa SMA Fons Vitae 1 Melalui Pelatihan Penulisan Review Film - Putri Rindu Kinasih (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Critical thinking is an important competency that needs to be developed in students in the digital age. However, various technological disruptions and fast-paced information consumption habits can hinder students' ability to conduct in-depth analysis and evaluation. Therefore, this community service activity aims to improve the critical thinking and English writing skills of Fons Vitae 1 Senior High School students through film review writing training. The activity took place on April 23, 2026, involving 20 participants from the English Club. The implementation method combined lectures, a screening of the short film “Jalanin Aja” by Joko Anwar, discussions, film review writing practice, and evaluation using a feedback questionnaire. The results of the activity showed that 95% of participants agreed that writing film reviews can improve their critical thinking skills. Furthermore, 90% of participants felt more confident expressing their opinions through writing, 90% considered the selected films relevant to their lives, and 95% stated that the activity was fun. Thus, film review writing training has proven to be an effective learning strategy for developing students' critical thinking and English writing skills.